DENTAL MORBIDITY IN CHILDREN AND ITS ASSOCIATION WITH BONE TISSUE METABOLISM MARKERS AND MINERAL METABOLISM LEVELS - Sukhomeylo, D.O.; Reyzvikh, O.E.; Shnaider, S.A.; Svitlychna, O.M.; Maslov, O.V.; Tsushko, I.O.; Burdeinyi, V.S. (World of Medicine and Biology, 2024)
The work was devoted to the clinical assessment of the state of hard tissues of teeth and periodontium in children who first visited a dentist and the establishment of a relationship with the level of markers of bone metabolism and mineral metabolism. Clinical trials were conducted with 109 children aged 2–5 years and 60 12–15-year-old adolescents who had not been previously sanitized. We studied the prevalence and intensity of caries in temporary and permanent teeth and an indicator of periodontal status. Laboratory tests involved determination of serum levels of total vitamin D (25-OH) (D2+D3), calcium, magnesium, and phosphorus. The results of the study indicate that there is a direct correlation between the indicators of children’s dental health, vitamin D metabolism and calcium-phosphorus metabolism. Establishing of the correlation between the level of essential micro- and macronutrients, as well as vitamin D in the organism of a child, in particular magnesium, and the prevalence of dental pathology in children allows to determine the directions of treatment and prevention measures aimed at improving the level of dental health.